Robust stability analysis of power electronic systems - Sumsurooah, Sharmila (2017)
Power electronics is the enabling technology that can put transportation on a more sustainable pathway. The key problem with power electronic (PE) systems is that they are prone to instability. Classical techniques are insufficient at assessing the stability of these systems, as they do not take into account the uncertain nature of physical systems. This thesis presents the structured singular value (SSV) method as an effective, reliable and robust stability analysis approach that justifiably incorporates uncertainties which are inherently present in physical systems.